2005
DOI: 10.1299/jsmea.48.151
|View full text |Cite
|
Sign up to set email alerts
|

A Closed Form Solution of a Crack in Magneto-Electro-Elastic Composites under Anti-Plane Shear Stress Loading

Abstract: In this paper, a closed form solution of a crack in magneto-electro-elastic composites under anti-plane shear stress loading is obtained for the permeable crack surface conditions. By using the Fourier transform technique, the problem can be solved with a pair of dual integral equations in which the unknown variable is the jump of the displacements across the crack surfaces. In solving the dual integral equations, the jump of the displacements across the crack surface is expanded in a series of Jacobi polynomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 10 publications
(6 reference statements)
2
6
0
Order By: Relevance
“…It is observed that for the permeable condition, the stress, electric and magnetic intensity factors of a cluster of multiple cracks are independent from the electric and magnetic loadings. This characteristic of the generalized intensity factors for permeable crack in magnetoelectroelastic materials has been reported in the literature for single crack and also for the case of three parallel non‐symmetric cracks . It should be noted that for a mathematical permeable crack with zero width, Gao et al showed that the energy release rate is independent of the applied electric/magnetic loading.…”
Section: Dislocation‐based Analysis Of Planes With Electromagneticallsupporting
confidence: 64%
See 2 more Smart Citations
“…It is observed that for the permeable condition, the stress, electric and magnetic intensity factors of a cluster of multiple cracks are independent from the electric and magnetic loadings. This characteristic of the generalized intensity factors for permeable crack in magnetoelectroelastic materials has been reported in the literature for single crack and also for the case of three parallel non‐symmetric cracks . It should be noted that for a mathematical permeable crack with zero width, Gao et al showed that the energy release rate is independent of the applied electric/magnetic loading.…”
Section: Dislocation‐based Analysis Of Planes With Electromagneticallsupporting
confidence: 64%
“…with kernels described after Eq. (28). It is noticed that for permeable condition, the stress field is identical to the stress field in an elastic solid.…”
Section: Field Components For System Of Permeable Cracksmentioning
confidence: 93%
See 1 more Smart Citation
“…The crack problems of multi-ferroic materials have gained significant interest from many researchers in the past two decades. Considerable academic efforts have been made on the analytical works for two-and three-dimensional crack problems, i.e., planar or anti-plane cracks [7,8,10,[12][13][14][15][16][17][18][19], penny-shaped cracks [20][21][22][23][24], elliptical cracks [25,26], and so forth.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the Stroh formalism method, the 2D Green's functions in EMTE media were given by Qin (2005). Zhou and Wang (2004) and Zhou et al (2005) studied a permeable crack subjected to an anti-plane shear loading by the Fourier transform method, and then found that the stress field was independent of the electric field and the magnetic flux.…”
Section: Introductionmentioning
confidence: 99%